(untitled) (Al-Farooq Journal of Sciences, 2026)
This field study was conducted to assess the natural regeneration capacity of the mastic tree, Pistacia lentiscus L., in areas affected by a previous wildfire in 2021 and in a degraded area impacted by environmental factors and human activities affecting its reproduction and growth rates. The study was carried out north of Ain Mara village, west of the city of Derna, Libya. Two study sites were selected, located on the northern and southern sides of the road. Each site was divided into two rectangular sectors (A and B), measuring 25 × 20 m (500 m²). Field visits were conducted over a period of two years (2021–2022), with two visits per year. A general description of each site was provided, including topography, soil characteristics, and associated plant species. The total number of trees and seedlings in each sector was recorded, and the crown cover percentage of Pistacia lentiscus was estimated, along with the crown cover percentage of the accompanying vegetation. The number of seedlings of Pistacia lentiscus and the vegetative shoots (root suckers) were monitored at the fire-affected site for two consecutive years. However, the results showed a complete absence of seedlings (zero seedlings) at both study sites. This may be attributed to the impact of wildfire on mature trees and seed viability at Site 1, while drought conditions, human disturbances, and overgrazing at Site 2 likely reduced the availability of suitable moisture conditions necessary for seed germination. Furthermore, tree and branch cutting has reduced canopy cover and shading, creating unfavorable conditions for seedling establishment. These combined factors have limited the species’ ability to produce new seedlings, resulting in the absence of young trees capable of replacing the existing population. Consequently, Pistacia lentiscus may face a serious risk of local extinction in this area in the future.